2016
DOI: 10.17795/minsurgery-41196
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curves in Robotic Rectal Cancer Surgery: A literature Review

Abstract: Background: Laparoscopic rectal cancer surgery offers several advantages over open surgery, including quicker recovery, shorter hospital stay and improved cosmesis. However, laparoscopic rectal surgery is technically difficult and is associated with a long learning curve. The last decade has seen the emergence of robotic rectal cancer surgery. In contrast to laparoscopy, robotic surgery offers stable 3D views with advanced dexterity and ergonomics in narrow spaces such as the pelvis. Whether this translates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…SPR-assisted surgery has been established, making it possible to perform robotic surgery with only one incision [ 21 22 23 ]. Research on the learning curve of surgery using robots has been reported, though studies on the learning curve of surgery using SPR have not been published [ 8 9 10 11 12 24 ]. In previous studies on robotic surgery, it has been suggested that the moving average line is useful in seeing the learning curve for managing OT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPR-assisted surgery has been established, making it possible to perform robotic surgery with only one incision [ 21 22 23 ]. Research on the learning curve of surgery using robots has been reported, though studies on the learning curve of surgery using SPR have not been published [ 8 9 10 11 12 24 ]. In previous studies on robotic surgery, it has been suggested that the moving average line is useful in seeing the learning curve for managing OT.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, there is a growing interest in the recently introduced technique of SPR-assisted surgery. Although numerous studies on the learning curve of conventional robotic surgery have been published, few studies as of yet have investigated the learning curve of SPR-assisted rectal cancer surgery [ 8 9 10 11 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on colorectal surgery, the learning curve stabilized after 15 to 25 cases [17,18,21]. Thus, the SPR learning curve does not differ significantly from that for other surgical methods, including laparoscopic surgery [19,25]. In contrast, when single-incision laparoscopic surgery and conventional laparoscopic surgery are compared, the learning curve for single-incision laparoscopic surgery requires more cases [14].…”
mentioning
confidence: 86%
“…This approach offers a 3-dimentional view, superior dexterity and ergonomics, and a better identification of anatomical structures in the confined pelvis [45]. Another advantage may be a shorter learning curve (estimated 15–44 procedures) [46]. Compared to laparoscopy, 3 meta-analyses [47-49] showed similar oncological outcomes and postoperative morbidity associated with the robotic approach.…”
Section: Local Extension Of Rectal Adenocarcinoma At Diagnosismentioning
confidence: 99%